(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
This article analyzes the current state of the art, scientific and theoretical foundations and practical results of the use of artificial intelligence and "Big Data" technologies in tax administration. The results obtained from the introduction of these technologies in world practice, in particular in the tax authorities of the OECD, the USA, Singapore and China, as well as the reforms being implemented in the Republic of Uzbekistan to digitize the tax system are considered. The impact of artificial intelligence on the efficiency of tax administration is quantitatively assessed based on statistical data for 2023-2025. The results of the study show that AI and Big Data technologies can increase the level of tax evasion detection to 82 percent, reduce the time of audits by 50 percent and significantly increase additional tax revenues. The article also puts forward practical recommendations for the modernization of tax administration for Uzbekistan.